القيادة الأخلاقية ودورها في تعزيز مبادىء حوكمة المنظمات دراسة تحليلية لآراء عينة من مديري الوحدات الإدارية في جامعة زاخو - إبراهيم, م.م. نيجرفان حجى; يوسف, أ.د. ميهفان شريف; مصطفى, م.م.ايوب على (Sulaimani Journal for Humanities, 2023)
The present research aims to know the role of the moral leadership in enhancing the principles of the governance of organizations at Zakho University, and the research relied on a group of main and sub -subsidies that have been tested in the field at a university and to achieve the research objectives of the questionnaire has been adopted as the main tool in collecting data for the current research from (65) individuals One of the directors of administrative units at the researched university, and data was analyzed using a group of statistical methods in the (SPSS V.25) program to analyze the relationship of the link and influence between the research variables, as a result, the research reached a number of conclusions, the most prominent of which indicates a significant correlation between the leadership Ethical and organizations ’governance, as well as a moral effect of moral leadership in the governance of organizations. In light of these conclusions, the researchers suggested the need to enhance and maintain the availability of advanced levels of moral leadership dimensions and harnessing them in order to improve the ability to enhance the principles of the governance of organizations.
Keywords: ethical leadership; Organizations Zakho University